Galilee and Gospel - Freyne, Sean (Brill Book Archive Part 1, ISBN: 9789004472495, 2002)
Please note that this title is only available to customers in the USA, Canada, and Mexico. NO salesrights for Rest of World. Galilee has long been a subject of fascination and scholarly inquiry because of its association with the formative periods of both Rabbinic Judaism and Early Christianity. Sean Freyne undertakes the difficult but essential task of bringing together literary and archaeological evidence to reconstruct the geographic, social, and religious world of Galilee in Hellenistic and Roman times. Both literary and archaeological evidence are essential for the study of early Judaism and the quest for the historical Jesus. Freyne fruitfully examines both areas of inquiry and makes substantial contributions to ongoing scholarly debates.